THE RESTORATION EFFORT OF PEAT MOSS ECOSYSTEM POSTCONFLAGRATION OF THE FOREST AND THE LAND IN LUKUN VILLAGE OF TEBING TINGGI TIMUR REGENCY - Ashaluddin Jalil; Yesi Yesi; Seger Sugiyanto (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
The conflagration continuously occurs with a different trend each year. Indonesian is especially an area that takes the root of peat moss labeled as the exporter of the smoke to the neighbor states and all at once it is not able to solve the conflagration completely because of various reasons. More or less 2 million hectares of the peat moss land has degradation and needs the recovery effort to be the job desk of the government to implement the restoration effort as soon as possible. Not only needing very big budget, that becoming the note is the society truly needs to support the activity to work well.  The goal of this research is namely: 1). identifying the factor of the forest and the land conflagration cause and its impact, 2) analyzing the restoration efforts of post conflagration disaster of the forest and the land. And the location of the research is in Lukun Village of Tebing Tinggi Timur Regency of Kepulauan Meranti Subdistrict. This research uses the qualitative descriptive approach. The causing factor of the conflagration disaster of the forest and the land is namely the natural condition and the human activity. The impact that is caused by the conflagration disaster of the forest and the land can be divided to be: the impact against the peat moss ecosystem and the impact against the society’s social economy. The effort that is implemented in the recovery of post conflagration disaster of the forest and the land is the ecosystem restoration and the revitalization of human’s economy.